The Genetic Basis of Plant Physiological Processes. - King, John (Oxford University Press, 1991)
This text explains how the study of fundamental plant physiological processes is being advanced through the science of genetics. The author adopts a case study approach to illustrate how defined genetic materials in mutants and plant variants are being used to explore plant physiology.